The Utilization of Moringa Leaves (Moringa Oleifera) as A Nutritional Supplement in Preventing Stunting in Toddlers: Nutrition Study and the Impact of Routine Consumption - Oktaviani Cahyaningsih; Okti Trihastuti Dyah Retnaningrum; Chusnul Zulaika (Indonesian Journal of Global Health Research, 2025)
The problem of stunting could pose a challenge for Indonesia's Golden 2045. Consuming moringa leaves (Moringa Oleifera) is one alternative to address the nutritional issues present in Indonesia. This plant has super nutritional content, beneficial for food and medicine. This study aims to evaluate the potential of using Moringa leaves as a nutritional supplement for toddlers in preventing stunting, and to determine whether there are differences in toddlers before and after being given food with added Moringa leaves. This research uses a Quasi-Experimental research design, employing quantitative data analysis, specifically a one group pretest post-test design. Sample of 30 respondents, The sampling technique used is Purposive Sampling with inclusion and exclusion criteria. There was an increase in body weight before and after the administration of moringa leaves, amounting to 2.01 kg, while for height, there was an increase of 1.3 cm before and after the administration of moringa leaves. There is a difference between the measurements taken before the addition of moringa leaves to the diet and those taken after. After the addition of moringa leaves to the diet, there was a positive outcome, with 30 respondents experiencing weight gain. Additionally, there was a difference in height measurements before and after the addition of moringa leaves to the diet. The conclusion of this study is that there is an increase in both body weight and height after the addition of moringa leaves to the diet.